Leading Innovative Projects: Essential Skills for Academic Faculty - Nancy Spector; Theodore Sectish (Association of American Medical Colleges, 2014)
Abstract Introduction Scholarly projects that are innovative and productive often are the result of the collaborative efforts of individuals on project teams. Project teams require leaders who will ensure that all aspects of the project are completed in a timely fashion and oversee the project to completion as well as manage the issues that arise on a day-to-day basis. As academic faculty progress in their careers, there are opportunities to lead projects in research, clinical innovations, curricular change, and organizational initiatives. In this educational module, we focus on leading a team for an innovative project. Methods This educational resource is designed as an interactive workshop that could vary in length from 60 to 90 minutes, depending on the number of activities that are done live during the workshop or assigned as homework afterwards. The session is divided into four sections and requires one or two workshop leaders, as well as additional facilitators who have some experience in leading a project team. An ideal venue would be one with flexible seating that allows for smooth transitions from didactic instruction to small group interactive activities. Results We have presented this workshop in conjunction with other workshop content within our own institutions and in several national venues. In these venues, 93-95% of participants (residents, fellows, chief residents, and academic faculty) agree/strongly agree that the workshop met its stated objectives. In addition, 100% of participants (residents, fellows, chief residents, and academic faculty) rated each of the following items as very good/excellent: content, organization, presentation, use of time and the quality of handouts and visual materials. Discussion Project teams require leaders who will ensure that all aspects of the project are completed in a timely fashion and oversee the project to completion as well as manage the issues that arise on a day-to-day basis. This educational resource is designed to provide instruction on effective team leadership.